2021
DOI: 10.4997/jrcpe.2021.405
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Long Covid in the Uk: A Single-Centre Observational Study

Abstract: IntroductionSince the World Health Organization declared the COVID-19 global pandemic in early March 2020, over 153 million coronavirus cases and 3.2 million deaths were reported worldwide. 1 The effective and rapid roll-out of the COVID-19 vaccine in the UK and other parts of the world has brought hope that the pandemic is coming to an end. 2,3 Unfortunately, the long-term devastating effects of COVID-19 are here to stay. There has been increasing attention recently about the longterm sequel of COVID-19 calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
4
7
0
Order By: Relevance
“…As shown in Table 1, sampling of participants in this analysis ensures the validity of this work without any potential problems regarding selection bias. Consistent with previous studies, our data revealed that fatigue and respiratory symptoms are the two leading complaints at almost the same level [27][28][29] . First, our data showed that long COVID has a dynamic nature of changeable manifestations throughout the clinical course in the majority of patients (Table 3), given the depressing impression that the clinical condition continuously improves and worsens over time, and the condition feels permanent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Table 1, sampling of participants in this analysis ensures the validity of this work without any potential problems regarding selection bias. Consistent with previous studies, our data revealed that fatigue and respiratory symptoms are the two leading complaints at almost the same level [27][28][29] . First, our data showed that long COVID has a dynamic nature of changeable manifestations throughout the clinical course in the majority of patients (Table 3), given the depressing impression that the clinical condition continuously improves and worsens over time, and the condition feels permanent.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Table 1, the sampling of participants in this analysis ensures the validity of this work without any potential problems regarding selection bias. Consistent with previous studies, our data revealed that fatigue and respiratory symptoms are the two leading complaints at almost the same level 36–38 …”
Section: Discussionsupporting
confidence: 92%
“…They speculated that COVID-19 pneumonia in our study at the time of the hospital admission might not be a reliable predictor of long COVID. 1 They claimed that the recent study by Evans et al found no link between the severity of pneumonia and the long COVID symptoms at 6 months; however, mechanical ventilation, female sex and middle age were risk factors for long COVID. 2…”
Section: Authors’ Replymentioning
confidence: 96%
“…Table 2 shows a summary of useful investigation tools for patients with PC19S. A Bangladesh cohort study showed a persistence of PC19S symptoms at 9 months ranging from 16.1% to 50% [ 92 , 93 ]. The mean duration of PC19S symptoms was 21.8 weeks and the length of PC19S was projected with a structural equation based on age, gender, smoking and prior functional limitations [ 92 ].…”
Section: Prognosis Of Pc19s Toolsmentioning
confidence: 99%